College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.4 - Average Rate of Change of a Function - 2.4 Exercises - Page 224: 16


(a) 12 (b) 6

Work Step by Step

We are given: $f(z)=1-3z^2$; $z=-2$, $z=0$ (a) We calculate the net change: $f(0)-f(-2)=[1-3(0)^{2}]-[1-3(-2)^{2}]=(1-3*0)-(1-3*4)=1- -11=12$ (b) We calculate the average rate of change: $\displaystyle \frac{f(0)-f(-2)}{0-(-2)}=\frac{12}{2}=6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.